PARESTHESIA FOLLOWING LOCAL ANESTHETIC ADMINISTRATION IN DENTISTRY - DR. M.P.SANTHOSH KUMAR (International Journal of Pharma and Bio Sciences, 2015)
Local anesthetics are the common drugs used in dentistry for several dental procedures. Although they are very safe, there are some reports of occurrence of paresthesia, a post anesthetic complication. Paresthesias can range from slight to complete loss of sensation and can be devastating for the patient.This article reviews the literature about the incidence of paresthesia induced by the administration of local anesthetic, which is not related to surgical trauma. Also, this article discusses the etiology of paresthesias, bias in the research studies, and presents recommendations for use of local anesthetics in clinical practice.